(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The transition into higher education represents one of the most cognitively and socially demanding developmental junctures in a learner’s academic trajectory. This study examines contemporary frameworks and evidence-based strategies aimed at cultivating adaptive readiness among first-year undergraduate students within rapidly evolving academic ecosystems. Drawing on a convergence of socio-constructivist theory, digital pedagogy, and institutional ecology perspectives, the investigation synthesises global best practices alongside empirical data gathered from four universities in Uzbekistan (n = 420). Findings reveal that integrated support architectures — encompassing mentorship scaffolding, adaptive learning technologies, and proactive wellbeing systems — reduce early attrition risk by up to 2.3-fold and improve first-semester academic performance indices by 31.5 percent compared to conventional enrolment approaches. The paper advances a culturally responsive adaptation model that harmonises Uzbek socio-educational values with twenty-first century pedagogical imperatives, offering transferable implications for post-Soviet and emerging-economy higher education contexts.